SPECIES COMPOSITION AND DISTRIBUTION OF MOLLUSCA AND ECHINODERMATA ON CORAL REEFS IN SURVEY ON AKADEMIK OPARIN RC IN 2016–2017 - Quang, Thai Minh; Tuyen, Hua Thai; Khang, Nguyen An (Vietnam Journal of Marine Science and Technology, 2019)
A study on the species composition and distribution of Mollusca and Echinodermata on coral reefs from Quang Tri to Binh Thuan was conducted during the field survey between Vietnam and Russia on the AKADEMIK OPARIN RC vessel in 2016 and 2017 at 39 reef stations. 150 species were identified belonging to 100 genera, 50 families, 22 orders, 7 classes distributed on coral reefs. The species composition of mollusca and echinodermata was different between study areas